Alcalinidade, cloretos, dureza e ph de amostras de água de poços nos municípios de alegrete, são gabriel e santa maria-rs - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Water has great importance for humanity and the impurity found in water reduces their quality and may pose risk to the health of living beings. Groundwaters obtained from wells usually are naturally protected from these impurities and pollutants, so this becomes an important alternative supply of the population. Analysis of samples collected in Alegrete, Santa Maria and San Gabriel-RS, in the years 2011 and 2012 were performed in the laboratory of chemistry and biochemistry at the Federal University of Pampa (UNIPAMPA) by potentiometric method and the method of titration where the parameters were performed: pH, alkalinity, hardness and chlorides. We analyzed 42 samples from the three municipalities and the results compared with current legislation. From these, tables were created with the values found in each municipality and comparison charts between them. According to the values determined, the municipalities of Santa Maria and San Gabriel are with all your samples all within the limits established. The municipality of Alegrete presented a sample with a pH of 5.6 that does not fall within the limit that is set between 6.0 to 9.5, and four samples with values of alkalinity, two with values above the threshold that is of 250mg.L-1 and two below the detection limit. According to these results for these parameters the waters of the wells in the cities of Santa Maria and San Gabriel are not considered a risk to community health. Although the city of Alegrete submit samples outside the set limits, the majority of the samples fall within the standards established by the existing agencies, it is necessary to continue studies in these municipalities in the form of monitoring to ensure the preservation and guarantee the quality of these wells.
Alkalinity, chlorides, hardness and pH of water samples from wells in the municipalities of alegrete, são gabriel and santa maria-rs
Keywords: Água - analise; Água - composição; Água - consumo; Água- purificação; Água - subterrânea; Water - analysis; Water - composition; Water - consumption; Water - purification; Underground water; CNPQ::CIENCIAS BIOLOGICAS